EKSPRESI VERBAL PENDERITA APRAXIA WICARA: KASUS GANGGUAN WICARA MURID SDN 2 BATU PUTIH KAB. BOMBANA - Batmang Batmang (Institut Agama Islam Negeri Kendari, 2016)
AbstractThis study aimed to obtain factual data of the verbal expression of speech apraxia people in order to know the forms of verbal expressions of patients with apraxia speech in terms of aspects of phonological, lexical aspect, and description of non-linguistic abilities. The study was conducted in SD Negeri 2 Batuputih, Southeast Sulawesi with a single subject, a fourth-grade student who suffered speech apraxia. This research was a case study that examined the behavior of language of the speech apraxia patients. The techniques used in data collection are observation, recording, question and answer, and interviews. The instrument used in data collection is, the pictures of objects, field notes, interview guide, and voice recorder. The data analysis was done by using an error analysis and contrastive analysis. The results obtained: (1) in terms of phonological aspects, the speech apraxia patients tended to have difficulty in reciting the phoneme, (2) in terms of lexical aspect, the verbal expressions of the apraxia speech patients are not meaningful at all, what people said just the unmeaning sounds, (3) linguistically speech apraxia patients are unable to express themselves the meaningful words but the non-linguistic one, the observed patients did not show any symptoms of abnormality.Keywords: Apraxia speech, verbal expression, impaired speech AbstrakPenelitian ini betujuan untuk memperoleh data faktual tentang ekspresi verbal penderita apraxia wicara agar dapat mengetahui bentuk-bentuk ekspresi verbal penderita apraxia wicara dalam hal aspek fonologi, aspek leksikal, dan gambaran tentang kemampuan non-linguistiknya. Penelitian dilakukan di SD Negeri 2 Batuputih, Sulawesi Tenggara dengan subjek tunggal seorang murid kelas IV yang menderita apraxia wicara. Penelitian ini mengkaji perilaku berbahasa pada penderita apraxia wicara. Teknik yang digunakan dalam pengumpulan data adalah: observasi, perekaman, tanya-jawab, dan wawancara. Alat yang digunakan dalam pengumpulan data adalah, gambar-gambar benda, catatan lapangan, panduan wawancara, dan alat perekam suara. Analisis data dilakukan dengan teknik analisis kesalahan dan analisis kontrastif. Hasil penelitian yang diperoleh: (1) dalam hal aspek fonologi penderita apraxia wicara cenderung mengalami kesulitan dalam melafalkan fonem; (2) dalam hal aspek leksikal, ekspresi verbal penderita apraxia wicara tidak memiliki makna sama sekali, apa yang diucapkan penderita hanyalah bunyi-bunyi yang tidak memiliki arti; (3) secara linguistik penderita apraxia wicara tidak mampu mengekspresikan diri dengan kata-kata yang bermakna tetapi secara non-linguistiknya, penderita yang diteliti tidak menunjukkan adanya gejala abnormalitas.Kata Kunci: Apraxia wicara, ekspresi verbal, gangguan wicara